The Effectiveness Of Software As Learning Media To Detect And Reduce Misconception In Stoichiometry Material - Reza Alfiyanti; Sukarmin Sukarmin (IJCER (International Journal of Chemistry Education Research), 2020)
In chemistry, an abstract material consists of three levels of representations that are macroscopic, sub-microscopic, and symbolic. However, many students have misconceptions due to the difficulty in understanding the relationship between the three levels representations. Misconceptions should be reduced or prevented as early as possible because it is resistant and difficult to change. Stoichiometry represents one example of chemistry material which consists of abstract concepts that usually lead to student misconceptions. The misconception in this material can be reduced if the wrong concept has already detected. Therefore it needed the tool that can detect and reduce these misconceptions. Software can be used as the tool to detect and reduce misconception because it has two functions as assessment and learning tool. Software must be said effective before it is used by student. So that this study aim is knowing the effectiveness of software to detect and reduce misconceptions in stoichiometry material. This study used Research and Development method. The result of this study shows that software is effective to detect and reduce misconceptions. It is proved by the average percentage of misconception shift to understand the concept about 80,13% which is categorized as effective.